Various estrus-synchronization programs for heifers - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1997)
Various programs of estrus synchronization have been tested during the last 6 years to determine the least costly and most efficacious for dairy heifer replacements. Four systems were tested: 1) a modified Ovsynch treatment (GnRH 7 days before PGF2 α followed by GnRH either at 24, 30, 33, 40, or 48 hr, with one fixed-time insemination 16 to 20 hr later); 2) a similar protocol that used GnRH 7 days before PGF 2α followed by insemination at estrus (GnRH + PGF 2α); 3) inseminations after one or two injections of PGF 2α given 14 days apart (PGF2α; heifers not detected in estrus after the second of two PGF 2α injections were given one fixed-time insemination at 72 hr); and 4) two injections of PGF2α given 14 days apart followed by GnRH at 33 hr, with one fixed-time insemination 16 to 18 hr later (2 x PGF2α + GnRH). The PGF2α treatment in which heifers were inseminated after detected estrus following one or two injections of PGF2α was the least costly for heifers and produced the best measures of fertility.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; GnRH; PGF2; Estrus synchronization; Heifers; Dairy